Desenvolvimento e caracterização de bolo de chocolate isento de glúten, contendo azuki (Vigna angularis) e chia (Salvia hispanica, L.) - Gohara, Aline Kirie (2013)
The current changes in the daily of world population reflect in drastic transformations of many aspects, especially in food consumption. Nowadays, most of foods do not have the minimum nutrients essential to the maintenance of human health, fact that aroused interest in enriched food developing and with functional appeal, mainly by food industries. The cakes ready for consumption have been acquiring great importance among the bakery products, since they are largely marketed, and hold the second position of the most consumed product ranking in this category, behind only of bread. There are gluten-free versions which can be consumed by celiac patients, however, these are still poor in many nutrients because they are composed primarily of rice flour. Azuki (Vigna angularis) is a legume widely produced and consumed in Asia, used in the various products manufacturing, especially in typical sweets. Chia (Salvia hispanica L.) is an angiosperm plant from the mint family (Lamiaceae) characterized as a grain from tropical and subtropical climate, widely consumed in pre-Columbian America by the Aztecs, in the region that includes Mexico and Guatemala. Both grains, azuki and chia, are considered rich source of many essential nutrients to good health maintenance. One of the most relevant aspects regard to nutrients is the mineral composition. Several minerals are essential for the maintenance of biological systems. Besides, sensorial aspects are very important factors for the development of new products. Factorial design enables evaluating the contribution of a specific ingredient on several characteristics of the final product and multivariate analysis enables extracting additional information when compared to the univariate analysis. This latter chemometric tool allows the pattern recognition, the gathering of information, reduction of data dimensionality and also the organization of data in a simpler structure, easier to understand. The principal component analysis (PCA) is based on perform linear comparisons of the original variables. The principal components (PC) are mutually orthogonal and explained variance decreases with increase in PC number. The aim of this study was to apply the Chemometrics to investigate the influence of the factors: percentages of chia and azuki added on gluten-free chocolate cake for the determination of proximal composition, energy, sensory aspects and the of minerals Ca, Cu, Fe, K, Mg, Mn and Zn.